Recent Progress in the Transfer of Graphene Films and Nanostructures. Issue 12 (5th November 2021) - Gao, Yanjing; Chen, Jielin; Chen, Guorui; Fan, Chunhai; Liu, Xiaoguo
Abstract: The one‐atom‐thick graphene has excellent electronic, optical, thermal, and mechanical properties. Currently, chemical vapor deposition (CVD) graphene has received a great deal of attention because it provides access to large‐area and uniform films with high‐quality. This allows the fabrication of graphene based‐electronics, sensors, photonics, and optoelectronics for practical applications. Zero bandgap, however, limits the application of a graphene film as electronic transistor. The most commonly used bottom‐up approaches have achieved efficient tuning of the electronic bandgap by customizing well‐defined graphene nanostructures. The postgrowth transfer of graphene films/nanostructures to a certain substrate is crucial in utilizing graphene in applicable devices. In this review, the basic growth mechanism of CVD graphene is first introduced. Then, recent advances in various transfer methods of as‐grown graphene to target substrates are presented. The fabrication and transfer methods of graphene nanostructures are also provided, and then the transfer‐related applications are summarized. At last, the challenging issues and the potential transfer‐free approaches are discussed. Abstract : In this review, recent progress in transfer methods of chemical vapor deposition graphene and graphene nanostructures is summarized. These transfer methods are discussed from the perspective of achieving clean, metal substrate reusable, and large‐scale transfer. The related graphene transfer‐based applications are also outlined. In the end, the challenges and potential transfer‐free approaches are presented.